(untitled) (Ibrahim Medical College Journal, 2016)
Drowning has been identified as a major cause of death in children in both developed and developing countries. Non-fatal drowning is several times higher than the fatal drowning. To describe the socio-demographic and environmental attributes of non-fatal drowning in rural children this community based descriptive study was conducted on 122 children having non-fatal drowning events within one year of study period. This study was undertaken in Raigonj sub-district of Sirajgonj district in Bangladesh. Mothers of those children were interviewed using a structured questionnaire. Out of all participants 56.6% children were 2-4 years of age and male-female ratio was almost equal. Of the total respondent mothers 55% were illiterate and 41.8% were below the age of 25 years. Seasonal variation was observed in non-fatal drowning. Rainy season (50.8%) appeared as the most risky period followed by summer (29.5%). Higher incidence occurred (53.3%) between 10 am to 2 pm of the day. Although most of the drowning occurred outside the home, 9% drowning occurred in water container (like drum, tub) within the home. Pond (50.5%) was found as the most common place among open water source. During the occurrence, 23% child was not accompanied by parents or any caregivers. At the time of drowning, 47.5% mothers were engaged with usual household work and were not present at the place of occurrence whereas 13% mothers were present around the place of occurance. Before drowning, 45.1% victim was either playing, bathing or swimming in the water. Only 10.7% needed resuscitation, 25% were taken to health centre and reached the health centre within an hour, about a fifth (22.6%) of them were admitted. Restriction in dangerous water activities, strengthening supervision of children might decrease the incidence of drowning while quick and effective medical response might prevent its fatal consequences. Ibrahim Med. Coll. J. 2015; 9(2): 37-41